Medusa tells all beauty missing, hair hissing - Davis, Rebecca Fjelland; Gilpin, Stephen (North Mankato, Minnesota Picture Window Books, a Capstone Imprint, 2014)
ntroduces the concept of point of view through Medusa's retelling of the classic Greek myth 'Medusa
Legends
a gift from book africa
1 2 13 15
Keywords: JUVENILE NONFICTION -- Social Science -- Folklore & Mythology; Medusa (Greek mythology) -- Juvenile literature